A narrow linewidth tunable single longitudinal mode Ga-EDF fiber laser. (May 2018) - Mohamed Halip, N.H.; Abu Bakar, M.H.; Latif, A.A.; Muhd-Yasin, S.Z.; Zulkifli, M.I.; Mat-Sharif, K.A.; Omar, N.Y.M; Mansoor, A.; Abdul-Rashid, H.A.; Mahdi, M.A.
Highlights: First demonstration on feasibility of laser device using Gallium-Erbium co-doped fiber. Simple single longitudinal mode laser setup integrating simple mode selectors. Excellent SLM output of 1.19 kHz linewidth with minimal power and wavelength dithering. Abstract: A tunable ring cavity single longitudinal mode (SLM) fiber laser incorporating Gallium-Erbium co-doped fiber (Ga-EDF) gain medium and several mode filtration techniques is demonstrated. With Ga-EDF, high emission power was accorded in short fiber length, allowing shorter overall cavity length and wider free spectral range. Tunable bandpass filter, sub-ring structure, and cascaded dissimilar fiber taper were utilized to filter multi-longitudinal modes. Each of the filter mechanism was tested individually within the laser cavity to assess its performance. Once the performance of each filter was obtained, all of them were deployed into the laser system. Ultimately, the 1561.47 nm SLM laser achieved a narrow linewidth laser, optical signal-to-noise ratio, and power fluctuation of 1.19 kHz, 61.52 dB and 0.16 dB, respectively. This work validates the feasibility of Ga-EDF to attain a stable SLM output in simple laser configuration.